TELAAH TARBAWI STYLE MANAJEMEN KELAS NABI MUHAMMAD SAW - Zaitur Rahem (Nurul Jadid University, 2017)
Modern schools today keep expanding. A fact that can be seen, the product material, material, and human beings of modern schooling continue to color changes and the times. There are great expectations, the schools developed the Muslim community is also in synergy with the changes and development of the times. Tarbawi style Prophet Muhammad should be presented in the field of Islamic education process. The style of the Prophet Muhammad in initiating, managing, and developing school’s system has been able to produce an extraordinary man. The Companions of the Prophet Muhammad be a reflection of the success of the school is implemented Prophet Muhammad since the early delivery of the teachings of Islam. Studies in this paper tries to lift the behavior of historical facts Uswatun Hasanah in creating civilization prestigious to next-generation Muslims. Through qualitative methods, and data collection techniques snawball sampling, data sources can be tracked easily. From data collected found, portraits in some persekolah Islam at Madura is less well ordered because of the lack of willingness of managers to assess the values taught by the Prophet valuable in the texts of Islam (Quran and Hadith).